Impacts of Land Use on Soil Erosion: RUSLE Analysis in a Sub-Basin of the Peruvian Amazon (2016–2022) - Moises Ascencio-Sanchez; Cesar Padilla-Castro; Christian Riveros-Lizana; Rosa María Hermoza-Espezúa; Dayan Atalluz-Ganoza; Richard Solórzano-Acosta (Geosciences)
The Peruvian Amazon faces an increasing threat of soil erosion, driven by unsustainable agricultural practices and accelerated deforestation. In Neshuya (Ucayali region), agricultural activity has intensified since 2014, but the effect on soil erosion is unknown. The present study aimed to evaluate the increase in erosion levels, at a sub-basin of the central–eastern Amazon of Peru, in a Geographic Information System (GIS) environment. The revised universal soil loss equation (RUSLE) model was used for assessing the effect of vegetation cover change from 2016 to 2022. In the Neshuya sub-basin (973.4 km2), the average erosion increased from 3.87 to 4.55 t ha−1 year−1, on average. In addition, there is great spatial variability in the values. In addition, 7.65% of the study area (74.52 km2) exceeds the soil loss tolerance limit (15 t ha−1 year−1). The deforestation rate was 17.99 km2 year−1 and by 2022 the forested area reached 237.65 km2. In conclusion, the transition from forest to farmland was related to the most critical erosion values. Unsustainable soil management practices can be the underlying explanation of changes in soil chemical and physical properties. Also, social dynamic changes and differences in landscape patterns play a role.